Writing and reading royal entertainments from George Gascoigne to Ben Jonson - Heaton, Gabriel (Oxford : Oxford University Press, 2010)
This study of Elizabethan and Jacobean royal entertainments including tiltyard speeches and court masques, looks in detail at the surviving material texts. It examines the 1602 Harefield entertainment, the 1575 Woodstock entertainment, the Merchant Taylors' and Theobalds' entertainments, and Ben Jonson's work for the Jacobean court.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English drama -- 17th century -- History and criticism; Masques, English -- History and criticism